2020
DOI: 10.48550/arxiv.2008.13014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

$DDK$ system in finite volume

Jin-Yi Pang,
Jia-Jun Wu,
Li-Sheng Geng

Abstract: The DDK 3-body system is supposed to be bound due to the strongly attractive interaction between the D meson and the K meson in the isospin zero channel. The minimum quark content of this 3-body bound state is ccqs with q = u, d. It will be an explicitly exotic tetraquark state once discovered. In order to confirm the phenomenological study of the DDK system, we can refer to lattice QCD as a powerful theoretical tool parallel to the experiment measurement. In this paper, a 3-body quantization condition scheme … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…If this is the case, in the sense that the deuteron is a bound state of proton and neutron, a naive but straight forward question to ask is whether DDK (and/or DD * K) can form 3-body bound states? A number of recent studies showed that they indeed bind [16][17][18][19][20]. Lately, the Belle Collaboration has performed the first experimental search for the existence of the DDK bound state and reported an upper limit for its production yield [21].…”
mentioning
confidence: 99%
“…If this is the case, in the sense that the deuteron is a bound state of proton and neutron, a naive but straight forward question to ask is whether DDK (and/or DD * K) can form 3-body bound states? A number of recent studies showed that they indeed bind [16][17][18][19][20]. Lately, the Belle Collaboration has performed the first experimental search for the existence of the DDK bound state and reported an upper limit for its production yield [21].…”
mentioning
confidence: 99%
“…An example for a particle-dimer theory with two dimer fields that can interact with each other can be found in ref. [93]. After integrating out the dimer fields, interactions with an odd number of pion fields can be obtained, e.g.…”
Section: Jhep04(2023)100mentioning
confidence: 99%
“…It should be mentioned that hadronic few-body systems have been extensively studied by different methods in the charm sector, such as the hidden charmed D DK [57] and D D * K [57-59], the BB K system [60], the πD D [61], ρD D [62], BD D [63] and Ξ cc Ξcc K [64], the singly charmed DN N [65], DK K [66,67], and N DK(N D K) [68], the doubly charmed DDK [69][70][71][72], BDD [63] and DD * K [58] systems, the triply charmed four-body DDDK [70], and the quadruply charmed Ξ cc Ξ cc K [64] systems. For recent reviews, see Refs.…”
Section: Introductionmentioning
confidence: 99%